Genotyping and rifampicin and isoniazid resistance in Mycobacterium bovis strains isolated from the lymph nodes of slaughtered cattle. (May 2017) - Franco, Marília Masello Junqueira; Ribeiro, Márcio Garcia; Pavan, Fernando Rogério; Miyata, Marcelo; Heinemann, Marcos Bryan; de Souza Filho, Antonio Francisco; Cardoso, Rosilene Fressatti; de Almeida, Aryadne Larissa; Sakate, Ricardo Ichiro; Paes, Antonio Carlos
Abstract: In developing nations, 10–20% of the human cases of tuberculosis are caused by Mycobacterium bovis . However, this percentage may be underestimated because most laboratories in developing countries do not routinely perform mycobacterial cultures, and only a few have the systems in place to identify M. bovis . There are few studies investigating genotypic diversity and drug resistance in M. bovis from animal and/or human infections. The genotypic diversity of M. bovis strains obtained from bovine lymph nodes were investigated by spacer oligonucleotide typing (spoligotyping) and mycobacterial interspersed repetitive unit–variable-number tandem repeat typing (MIRU-VNTR). The phenotypic resistance to isoniazid and rifampicin and MIC values of the isolates were determined using the resazurin microtiter assay plate method (REMA). The evaluation of the possible genetic basis for such resistance was performed with GenoType MTBDR plus . Sixty-seven isolates were obtained, of which 11 (16%) were MDR-TB, 8 (12%) were isoniazid-resistant, and 2 (3%) were rifampicin-resistant. Mutations associated with drug resistance were not found. Genotyping techniques enabled the grouping of the strains into 12 clusters and 21 isolates with unique profiles. The high frequency of M. bovis reinforces the impact of the pathogen as a major causal agent of bovine tuberculosis in the study area. The resistance of the strains to drugs used for first-line treatment of human tuberculosis raises public health concerns. Further studies are required to elucidate the basis of drug resistance and genotypic diversity in M. bovis .